Manipulation of Endogenous Trypsin Proteinase Inhibitor Production in Nicotiana attenuata Demonstrates Their Function as Antiherbivore Defenses - Zavala, Jorge A. (The American Society for Plant Biologists, 2004)
Evidence for the in planta defensive function of trypsin protease inhibitors (TPIs) comes from observations of enhanced herbivore resistance after heterologous TPI expression or the manipulation of signal cascades that activate numerous defense responses, including TPI production; no studies have altered the expression of an endogenous pi gene to examine defensive function. We isolated two genes with seven- and six-repeat TPI domains from Nicotiana attenuata from the potato (Solanum tuberosum) PI-II family. To determine whether endogenous TPIs in N. attenuata function defensively against the native herbivores, hornworm (Manduca sexta) and mirids (Tupiocoris notatus), we expressed 175 bp of the seven-domain pi from N. attenuata in an antisense orientation in a TPI-producing genotype to reduce TPI expression and expressed the full-length seven-domain pi in a sense orientation under control of a constitutive promoter to restore TPI activity in a natural genotype from Arizona unable to produce TPIs. Constitutive and inducible TPI production in two antisense lines were diminished by 80% to 90% and 33% to 52%, respectively, and sense expression restored 67% of the activity found in the TPI-producing genotype after caterpillar attack in the TPI-deficient A genotype. Hornworm larvae fed on genotypes with low or no TPI activity grew faster, had higher survivorship, and produced heavier pupae than those that fed on genotypes with high TPI activity. T. notatus showed higher preference for genotypes with low or no TPI activity than for genotypes with high TPI levels. We conclude that endogenous TPIs are an effective defense against these native herbivores.